Comparison of glial fibrillary acidic protein-immunoglobulin G-associated myelitis with myelin oligodendrocyte glycoprotein-immunoglobulin G-associated myelitis - Sun, Mengyang; Liu, Hao; Zhu, Bingqing; Liu, Yang; Li, Aijia; Wang, Limei (Frontiers in Neurology, 2023)
Objective Glial fibrillary acidic protein-immunoglobulin G (GFAP-IgG)-associated myelitis and myelin oligodendrocyte glycoprotein-IgG (MOG-IgG)-associated myelitis have rarely been compared. Therefore, this study aimed to explore the clinical, laboratory, and imaging features of them to identify the differences. Methods Overall, 14 and 24 patients with GFAP-IgG-and MOG-IgG-associated myelitis, respectively, were retrospectively screened and included in the study. Results Among the 14 patients with GFAP-IgG-associated myelitis, the condition was more common in males (71.4%), with a median age of onset of 36.5 years, and more common in adults than in children (35.7%). In contrast, among the 24 patients with MOG-IgG-associated myelitis, the condition was equally divided between males and females, with a median age of onset of 9.5 years and more in children (66.7%) than in adults. The median age of onset of GFAP-IgG-associated myelitis was later than that of the MOG-IgG group. Isolated myelitis was rare in both groups. Elevated cerebrospinal fluid (CSF) protein levels were more prevalent in patients with GFAP-IgG-associated myelitis (64.3%) than in those with MOG-IgG-associated myelitis (16.7%) (p < 0.05), whereas patchy gadolinium enhancement of the cerebral lesion site was less common in patients with GFAP-IgG-associated myelitis than in those with MOG-IgG associated myelitis (p < 0.05). Six patients had a combination of other neurological autoantibodies, the specific mechanism of the overlapping antibodies remains unclear. Conclusion Cerebrospinal fluid analysis and gadolinium enhanced MRI examination may help to distinguish the two kinds of myelitis.